Change of Serum Biomarkers to Post-Thrombolytic Symptomatic Intracranial Hemorrhage in Stroke - Cui, Yu; Wang, Xin-Hong; Zhao, Yong; Chen, Shao-Yuan; Sheng, Bao-Ying; Wang, Li-Hua; Chen, Hui-Sheng (Frontiers in Neurology, 2022)
Background Symptomatic intracranial hemorrhage (sICH) is a terrible complication after intravenous alteplase in stroke, and numerous biomarkers have been investigated. However, the change of biomarkers to sICH has not been well determined. Aim To investigate the association between the change of biomarkers and sICH. Methods This is a prospective cohort study, and patients with sICH within 24 h after thrombolysis were enrolled, while patients without sICH were matched by propensity score matching with a ratio of 1:1. The blood samples were collected before and 24 h after intravenous thrombolysis (IVT), and preset 49 serum biomarkers were measured by microarray analysis. Protein function enrichment analyses were performed to detect the association between the change of biomarkers and sICH. Results Of consecutive 358 patients, 7 patients with sICH in 24 h were assigned to the sICH group, while 7 matched patients without any ICH were assigned to the non-sICH group. A total of 9 biomarkers were found to significantly change before vs. after thrombolysis between groups, including increased biomarkers, such as brain-derived neurotrophic factor, C-C motif chemokine ligand (CCL)-24, interleukin (IL)-6, IL-10, IL-18, and vascular endothelial growth factor, and decreased biomarkers, such as CCL-11, intercellular adhesion molecule-1, and IL-7. Conclusions This is the first study to identify changes in serum biomarkers in patients with sICH after IVT, and found that 6 neuroinflammatory and 3 neuroprotective biomarkers may be associated with brain injury following post-thrombolytic sICH. Clinical Trial Registration https://www.clinicaltrials.gov, identifier: NCT02854592.